S_grubbing_transect ... - Virve.Ravolainen@Npolar.No (NPI, 2025)
Grubbing is recorded in 30 meters transects and in the vegetation types moss tundra, disturbed moss tundra and dryas ridge. The categories recorded are presence of picking, bulldozing and cratering per centimeter. In the datsheets, the presence of each category in each transect is summed up. The dataset is under embargo, with new datasets uploaded on December 31st, two years after being collected. Older versions of the dataset are publicly available for download. This version includes data from 2019-2022 ...